Design of novel lipidated peptidomimetic conjugates for targeting EGFR heterodimerization in HER2 + cancer. Issue 22 (1st December 2018) - Naik, Himgauri; Gauthier, Ted; Singh, Sitanshu; Jois, Seetharama
Graphical abstract: Highlights: A peptidomimetic-lipid conjugate was designed to inhibit HER2:HER3 dimerization. HER2 dimerization with EGFR receptors is important in lung and breast cancer. Conjugate exhibited antiproliferative activity in HER2 + lung cancer cells. The conjugate of stearic acid was shown to bind to HER2 protein specifically. The conjugate exhibited better stability in serum compared to peptidomimetic. Abstract: The human epidermal growth factor receptor (EGFR) family is known to be involved in cell signaling pathways. The extracellular domain of EGFR consists of four domains, of which domain II and domain IV are known to be involved in the dimerization process. Overexpression of these receptors is known to play a significant role in heterodimerization of these receptors leading to the development of cancer. We have designed peptidomimetic molecules to inhibit the EGFR heterodimerization interaction that have shown antiproliferative activity and specificity for HER2-positive cancer cell lines. Among these, a peptidomimetic, compound5, exhibited antiproliferative activity at low nanomolar concentrations in HER2-overexpressing cancer cell lines. To improve the stability of this peptidomimetic, we have designed and synthesized a novel conjugate of peptidomimetic compound5 with a lipid, stearic acid. The antiproliferative activity of this conjugate was evaluated in HER2-positive cancer cell lines. Results suggested that the conjugate exhibited selective antiproliferative activity in HER2-overexpressing breast and lung cancer cell lines and was able to block HER2:HER3 heterodimerization. Also, the conjugate showed improved stability with a half-life of 5 h in human serum compared to the half-life of 2 h for parent compound5 . The binding affinity of the conjugate to HER2 protein was evaluated by SPR analysis, and the mode of binding of the lipid conjugate to domain IV of HER2 protein was demonstrated by docking analysis. Thus, this novel lipid conjugate can be used to target HER2-overexpressing cancers.